Pengaruh Struktur Modal, Risiko Sistematis dan Likuiditas Terhadap Return Saham (pada Perusahaan di LQ45 Tahun 2018-2020) - Islamiyanti, Erni; Sari, Herlinda Maya Kumala (Academicia Globe: Inderscience Research, 2020)
This study aims to determine the effect of capital structure, systematic risk and liquidity on stock returns (in companies at LQ45 in 2018-2020). The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 43 of the LQ45 companies listed on the Indonesia stock exchange in 2018-2020. The data used is secondary data. The data analysis method used in this research is multiple linear regression. The results of this study indicate that the capital structure has a partial effect on stock returns. Systematic risk partially affects stock returns. Liquidity partially affects stock returns. Capital structure, systematic risk, and liquidity simultaneously affect stock returns.